(untitled) (Comprehensive Journal of Science, 2025)
This study focuses on analyzing vibration characteristics in steam turbines and assessing their direct impact on operational efficiency. The research aims to identify the primary mechanical causes of vibration, including dynamic imbalance, shaft misalignment, and blade wear or damage. Advanced vibration spectrum analysis techniques, specialized engineering software, and field measurement data obtained from operating turbines under industrial conditions were employed. The results indicate that mechanical vibrations significantly contribute to the reduction of operational efficiency and the shortening of the turbine’s service life, thereby affecting overall performance. The study recommends adopting predictive maintenance strategies based on smart sensor systems, enhancing the design of supporting structures, and implementing precise dynamic balancing adjustments. Furthermore, the findings were compared with several previous studies to validate their accuracy and highlight areas of agreement and divergence. The study employs an experimental methodology supported by numerical simulations to test the proposed hypotheses and develop practical engineering solutions that enhance operational performance and minimize mechanical failures